Radiation-resistant photo-thermal dual-curing conductive adhesive and preparation method thereof

The radiation-resistant and photothermal dual-curing conductive adhesive prepared by modified powder solves the problem of easy aging of conductive silver paste in the space environment, and realizes high reliability and durability of conductive adhesive in spaceborne optical modules, adapting to harsh temperature changes.

CN121046002APending Publication Date: 2025-12-02WUHAN HUAGONG GENUINE OPTICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511169073.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-20
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Existing conductive silver paste is prone to aging and failure in the harsh environment of space, affecting the stability and reliability of the optical chips in spaceborne optical modules.

Method used

A radiation-resistant, photothermal dual-curing conductive adhesive was prepared using modified powder. The mixture of conductive filler, metallic carbon nanotubes, and nano-metal oxides was modified with a modifier and combined with photocuring and thermal curing technologies to form a dense structure that blocks radiation particles. Early photocuring was then performed at room temperature.

Benefits of technology

It significantly improves the radiation resistance and durability of conductive adhesive, enhances the reliability and bonding yield of optical modules in the starry sky environment, and adapts to changes in cosmic temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of aerospace optical device packaging, in particular to an anti-irradiation photo-thermal dual-curing conductive adhesive and a preparation method thereof. Comprising the following components in parts by weight: 10-30 parts of epoxy resin, 1-5 parts of a thermal initiator, 2-4 parts of a photoinitiator, 30-75 parts of modified powder, 0-3 parts of a coupling agent, 5-10 parts of an epoxy reactive diluent and 0-10 parts of a flame retardant, the modified powder is prepared by modifying a mixture of a conductive filler, a metallic carbon nanotube and a nano metal oxide by using a modifier. According to the conductive adhesive, the modified powder is added into the conductive adhesive, so that the problem of compatibility of a formula can be solved, warping of the conductive adhesive is effectively reduced, the conductivity of the conductive adhesive is also improved, and meanwhile, the metallic carbon nanotubes form a coaxial circular tube structure by carbon atoms arranged in a hexagonal manner, so that cosmic rays can be absorbed, and the conductivity of the conductive adhesive is improved. The conductive filler and the nano metal oxide powder can fill the gaps between the circular tubes and form a compact structure, and radiation particles can be effectively blocked, so that the radiation resistance of the conductive adhesive is remarkably improved, and the durability and reliability of the optical module in a starry sky environment are greatly improved under the condition of ensuring chip packaging and bonding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical device packaging technology for aerospace applications, specifically to a radiation-resistant, photothermal dual-curing conductive adhesive and its preparation method. Background Technology

[0002] In recent years, the global satellite communication market has continued to grow, and the development of optical modules suitable for satellite communication has become a key driver of this field. Compared to ordinary optical modules, spaceborne optical modules need to adapt to the harsh environment of space. On the one hand, they need to withstand the damage caused by mixed space radiation from the sun, galactic cosmic rays, and Earth's radiation belts, namely gamma rays, high-energy protons, and charged particles. On the other hand, they need to overcome the severe temperature variations in space. The external temperature of spacecraft can vary from -270°C to 150°C, and the temperature difference between the sunlit and shaded sides can reach several hundred degrees Celsius. The temperature difference of the module's working environment inside the spacecraft is also more stringent than on Earth, typically requiring a range of -55°C to 100°C.

[0003] In spaceborne optical modules, lasers, detectors, and optical fiber transmission units are the most sensitive components and require special protection. Currently, conductive silver paste is used for packaging optical chips in spaceborne optical modules. However, under the harsh and variable environmental stresses of space for extended periods, the conductive silver paste is prone to aging and failure, directly affecting the stability and reliability of the optical chips. Summary of the Invention

[0004] In order to overcome the shortcomings of the existing technology, the purpose of this invention is to provide a radiation-resistant photothermal dual-curing conductive adhesive and its preparation method, which greatly increases the durability and reliability of the optical module in the starry sky environment while ensuring chip packaging and bonding.

[0005] To achieve the above objectives, the technical solution of the present invention is a radiation-resistant, photothermal dual-curing conductive adhesive, comprising the following components by weight: 10-30 parts epoxy resin, 1-5 parts thermal initiator, 2-4 parts photoinitiator, 30-75 parts modified powder, 0-3 parts coupling agent, 5-10 parts epoxy reactive diluent, and 0-10 parts flame retardant; the modified powder is prepared by modifying a mixture of conductive filler, metallic carbon nanotubes, and nano-metal oxides with a modifier.

[0006] As one embodiment, the amount of the conductive filler is 20-50% of the total mass of the conductive adhesive; the amount of the metallic carbon nanotubes is 8-26% of the total mass of the conductive adhesive; and the amount of the nano-metal oxide is 10-25% of the total mass of the conductive adhesive.

[0007] As one embodiment, the conductive filler includes at least one of conductive mica powder, conductive titanium dioxide, conductive barium sulfate, conductive silicon dioxide, silver-plated copper powder, silver-plated nickel powder, and silver-plated graphite; the nano-metal oxide includes at least one of nano-tin oxide, nano-tantalum oxide, and nano-zirconia; and the modifier is a silane coupling agent.

[0008] As one embodiment, the modified powder is prepared by stirring and mixing conductive filler, metallic carbon nanotubes, nano-metal oxides and deionized water evenly, adjusting the pH value to acidic, then adding a mixed solution of modifier and anhydrous ethanol to carry out the modification reaction, cooling to room temperature after the reaction is completed, centrifuging and taking the lower precipitate to disperse in anhydrous ethanol, then sonicating and drying to obtain the modified powder.

[0009] As one embodiment, the ratio of the total mass of the conductive filler, the metallic carbon nanotubes, and the nano-metal oxides to the mass of the modifier is 100:(5-12).

[0010] As one embodiment, the epoxy resin includes thermosetting epoxy resin and photocuring epoxy resin, and the mass ratio of the thermosetting epoxy resin to the photocuring epoxy resin is (1-5):1.

[0011] As one embodiment, the thermal initiator is a cationic thermal initiator; the photoinitiator includes a free radical photoinitiator and a cationic photoinitiator, and the mass ratio of the two is (1-2):(1-2).

[0012] The present invention also provides a method for preparing the radiation-resistant photothermal dual-curing conductive adhesive as described in any one of the above claims, comprising the following steps:

[0013] S1. The reactor is stirred at the first speed, and epoxy resin and part of epoxy reactive diluent are added while stirring.

[0014] S2. Increase the rotation speed to the second speed and gradually add the modified powder while stirring;

[0015] S3. Increase the rotation speed to the third speed and stir until the modified powder is completely and evenly dispersed;

[0016] S4. Adjust the speed to the second speed, add the flame retardant while stirring, and stir until the mixture is evenly mixed.

[0017] S5. Keep the rotation speed at the second speed and add the thermal initiator, photoinitiator and coupling agent while stirring;

[0018] S6. Stop stirring, test the viscosity of the mixed slurry, and use the remaining epoxy reactive diluent to adjust the mixed slurry to the target viscosity.

[0019] As one implementation method, in step S3, after stirring until the modified powder is completely and evenly dispersed, the fineness of the mixed slurry is tested. If it does not meet the standard, stirring needs to be continued until the target fineness is reached. During the stirring process, the temperature of the mixed slurry is kept at 10-35℃.

[0020] As one implementation method, the first rotational speed is 100-400 r / min, the second rotational speed is 800-1000 r / min, and the third rotational speed is 1200-1500 r / min.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The present invention obtains a modified powder by adding a modifier to a mixture of conductive filler, metallic carbon nanotubes and nano metal oxides in conductive adhesive. This not only solves the problem of formula compatibility and effectively reduces the bleeding of conductive adhesive, but also improves the conductivity of conductive adhesive. Meanwhile, the metallic carbon nanotubes are composed of coaxial circular tubes with carbon atoms arranged in hexagons, which can absorb cosmic rays. The conductive filler and nano metal oxide powder can fill the gaps between the tubes and form a dense structure, which can effectively block radiation particles, thereby significantly improving the radiation resistance of conductive adhesive. While ensuring chip packaging and bonding, it greatly increases the durability and reliability of optical modules in the starry sky environment.

[0023] (2) By adding photocurable epoxy resin and photoinitiator to the conductive adhesive, the conductive adhesive has the dual curing effect of thermal curing and photocuring. It can be photocured in time at room temperature, avoiding the heating in the thermal curing process, thereby reducing the precipitation of organic matter in the curing process. By using modified powder and photothermal dual curing method, the bleeding phenomenon of conductive adhesive can be significantly reduced, and the bonding yield of the optical chip after chip mounting and packaging can be increased.

[0024] (3) The conductive adhesive of the present invention can withstand the harsh temperature changes in the universe and is especially suitable for the encapsulation of optical chips in spaceborne optical modules. Detailed Implementation

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] This invention provides a radiation-resistant, photothermal dual-curing conductive adhesive, comprising the following components by weight: 10-30 parts epoxy resin, 1-5 parts thermal initiator, 2-4 parts photoinitiator, 30-75 parts modified powder, 0-3 parts coupling agent, 5-10 parts epoxy reactive diluent, and 0-10 parts flame retardant; the modified powder is prepared by modifying a mixture of conductive filler, metallic carbon nanotubes, and nano-metal oxides using a modifier.

[0027] This embodiment uses a modified powder prepared by adding a modifier to a mixture of conductive filler, metallic carbon nanotubes, and nano-metal oxides to a conductive adhesive. This not only solves the formulation compatibility problem and effectively reduces conductive adhesive bleeding, but also improves the conductivity of the conductive adhesive. Meanwhile, the metallic carbon nanotubes, composed of coaxial cylindrical structures of hexagonally arranged carbon atoms, can absorb cosmic rays. The conductive filler and nano-metal oxide powder can fill the gaps between the cylindrical tubes and form a dense structure, which can effectively block radiation particles, thereby significantly improving the radiation resistance of the conductive adhesive. While ensuring chip packaging and bonding, this greatly increases the durability and reliability of the optical module in the cosmic environment.

[0028] Furthermore, the amount of the conductive filler is 20-50% of the total mass of the conductive adhesive; the amount of the metallic carbon nanotubes is 8-26% of the total mass of the conductive adhesive; and the amount of the nano-metal oxides is 10-25% of the total mass of the conductive adhesive. Specifically, the amount of metallic carbon nanotubes is 8-26% of the total mass of the conductive adhesive. As the amount of metallic carbon nanotubes increases, the conductivity of the conductive adhesive increases. However, when the amount of metallic carbon nanotubes is 0.5-0.8%, it forms an antistatic region; when the amount is 8%, it forms a semiconductor; and when the amount exceeds 26%, the conductivity of the conductive adhesive no longer increases.

[0029] Furthermore, the conductive filler includes at least one of conductive mica powder, conductive titanium dioxide, conductive barium sulfate, conductive silicon dioxide, silver-plated copper powder, silver-plated nickel powder, and silver-plated graphite; the nano-metal oxide includes at least one of nano-tin oxide, nano-tantalum oxide, and nano-zirconia; and the modifier is a silane coupling agent. The conductive mica powder has a sheet-like structure and a large specific surface area, enabling it to absorb cosmic rays. When the modified powder is a mixture of conductive mica powder, metallic carbon nanotubes, and nano-metal oxides, the radiation resistance of the conductive adhesive can be improved.

[0030] In this embodiment, the modified powder is prepared by stirring and mixing conductive filler, metallic carbon nanotubes, nano-metal oxides and deionized water evenly, adjusting the pH value to acidic, then adding a mixed solution of modifier and anhydrous ethanol to carry out the modification reaction. After the reaction is completed, the mixture is cooled to room temperature, centrifuged and the lower precipitate is dispersed in anhydrous ethanol, then sonicated and dried to obtain the modified powder.

[0031] Specifically, the pH value is adjusted to acidic by slowly adding an acetic acidity regulator; the modification reaction is completed by heating to 55-75℃ and holding the reaction at that temperature for 1-3 hours; the ultrasonic treatment time is 1-2 hours; and the drying is carried out at 50-85℃ for more than 12 hours; the modifiers include γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560, CAS: 2530-83-8) and γ-methacryloyloxypropyltrimethoxysilane (K At least one of the following: H570, CAS: 2530-85-0, 3-mercaptopropyltrimethoxysilane (KH590, CAS: 4420-74-0), 3-mercaptopropyltriethoxysilane (KH-580, CAS: 14814-09-6), vinyltrimethoxysilane (KH-171, CAS: 2768-02-7), and vinyltriethoxysilane (KH1510, CAS: 78-08-0).

[0032] Further, the ratio of the total mass of the conductive filler, the metallic carbon nanotubes, and the nano-metal oxide to the mass of the modifier is 100:(5-12). Even further, the ratio of the total mass of the conductive filler, the metallic carbon nanotubes, and the nano-metal oxide, the mass of the modifier, and the volume of deionized water is 100g:(5-12)g:1000mL.

[0033] In some embodiments, the epoxy resin includes a thermosetting epoxy resin and a photocurable epoxy resin, wherein the mass ratio of the thermosetting epoxy resin to the photocurable epoxy resin is (1-5):1. The thermosetting epoxy resin includes at least one of hydrogenated bisphenol A epoxy resin and alicyclic epoxy resin; the photocurable epoxy resin includes at least one of phenolic epoxy acrylate, o-cresol epoxy acrylate, and silicone-modified epoxy acrylate. The initiator includes a thermal initiator and a photoinitiator, allowing unreacted monomers during photocuring to continue polymerizing during thermocuring, ensuring complete curing of the adhesive, thereby increasing strength and reducing volatiles after curing.

[0034] In some embodiments, the thermal initiator is a cationic thermal initiator; the photoinitiator includes a free radical photoinitiator and a cationic photoinitiator, and the mass ratio of the two is (1-2):(1-2).

[0035] The cationic thermal initiator includes at least one of blocked phosphate cationic thermal initiators and onium salt cationic thermal initiators; the blocked phosphate cationic thermal initiator includes at least one of cationic thermal initiators CTI-100, CTI-150, and CTI-200; the onium salt cationic thermal initiator includes at least one of thioonium salt cationic thermal initiators, pyridinium salt cationic thermal initiators, phosphonium salt cationic thermal initiators, and iodonium salt cationic thermal initiators. Specifically, the iodonium salt cationic thermal initiator can be p-(octyloxyphenyl)phenyliodonium hexafluoroantimonate, etc., and the thioonium salt cationic thermal initiator can be phenylthiophenyl-diphenylthiodonium hexafluorophosphate, etc.

[0036] The free radical photoinitiator includes at least one of the free radical photoinitiators TPO, 819, ITX, 369, 907, 1173, 184, and 651; the cationic photoinitiator is a diaryliodomonium salt or a triarylthionium salt, including but not limited to at least one of p-(octoxyphenyl)phenyliodomonium hexafluoroantimonate, phenylthiophenyl-diphenylthionium hexafluorophosphate, and triarylthionium hexafluorophosphate.

[0037] In this embodiment, the coupling agent includes at least one of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560, CAS:2530-83-8), γ-methacryloyloxypropyltrimethoxysilane (KH570, CAS:2530-85-0), 3-mercaptopropyltrimethoxysilane (KH590, CAS:4420-74-0), 3-mercaptopropyltriethoxysilane (KH-580, CAS:14814-09-6), vinyltrimethoxysilane (KH-171, CAS:2768-02-7), and vinyltriethoxysilane (KH1510, CAS:78-08-0).

[0038] Epoxy reactive diluents include at least one of monofunctional reactive diluents, difunctional reactive diluents, and polyfunctional reactive diluents. Specifically, they can be at least one of β-hydroxyethyl methacrylate (HEMA), 1,6-hexanediol diacrylate (HDDA), oxetanes, and ester ring epoxy diluents.

[0039] Flame retardants include at least one of organic and inorganic flame retardants; the conductive adhesive of this embodiment can not only resist the harsh temperature changes of space, but also improve the flame retardant performance of aerospace optical devices by adding appropriate amounts of flame retardants, organic flame retardants and / or inorganic flame retardants.

[0040] This embodiment also provides a method for preparing the radiation-resistant photothermal dual-curing conductive adhesive as described in any one of the above embodiments, comprising the following steps:

[0041] S1. The reactor is stirred at the first speed, and epoxy resin and part of epoxy reactive diluent are added while stirring.

[0042] S2. Increase the rotation speed to the second speed and gradually add the modified powder while stirring;

[0043] S3. Increase the rotation speed to the third speed and stir until the modified powder is completely and evenly dispersed;

[0044] S4. Adjust the speed to the second speed, add the flame retardant while stirring, and stir until the mixture is evenly mixed.

[0045] S5. Keep the rotation speed at the second speed and add the thermal initiator, photoinitiator and coupling agent while stirring;

[0046] S6. Stop stirring, test the viscosity of the mixed slurry, and use the remaining epoxy reactive diluent to adjust the mixed slurry to the target viscosity.

[0047] In step S1 of this embodiment, a portion of epoxy reactive diluent is added, while a portion of epoxy reactive diluent is reserved. After stopping stirring in step S6, the viscosity of the mixed slurry is tested, and a certain amount of the reserved epoxy reactive diluent is added as needed to adjust the mixed slurry to the target viscosity.

[0048] In step S1, after adding the materials, mix for 5-10 minutes, and reserve 2-5 parts of epoxy reactive diluent for viscosity adjustment in step S6.

[0049] In step S2, when adding the modified powder, the modified powder should be added gradually in accordance with the stirring speed, and the appropriate feeding speed is to ensure that too much powder does not accumulate in the middle of the stirring paddle.

[0050] In step S3, stir rapidly for 30-60 minutes at the third rotation speed until the modified powder is completely and evenly dispersed in the epoxy resin.

[0051] Furthermore, in step S3, after stirring until the modified powder is completely and evenly dispersed, the fineness of the mixed slurry is tested. If it does not meet the standard, stirring needs to be continued until the target fineness is reached. During the stirring process, the temperature of the mixed slurry is kept at 10-35℃. If it exceeds 35℃, the stirring speed needs to be reduced and the cooling water needs to be turned on to cool it down.

[0052] Furthermore, the first rotational speed is 100-400 r / min, the second rotational speed is 800-1000 r / min, and the third rotational speed is 1200-1500 r / min.

[0053] In step S4, after adding the flame retardant, stir for 5-10 minutes.

[0054] In step S5, after adding the thermal initiator, photoinitiator, and coupling agent, stir for 5-10 minutes.

[0055] Example 1: This example also provides a radiation-resistant photothermal dual-curing conductive adhesive, comprising the following components by weight: 19.6 parts hydrogenated bisphenol A epoxy resin, 5.8 parts phenolic epoxy acrylate, 73 parts modified powder, 1.2 parts cationic thermal initiator CTI-100, 1.2 parts free radical photoinitiator 819, 1.5 parts p-(octyloxyphenyl)phenyliodonium hexafluoroantimonate, 6 parts oxetane epoxy reactive diluent, 2.5 parts γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), and 6 parts organic flame retardant.

[0056] The preparation method of the modified powder is as follows: 30 parts of silver-plated copper powder, 18 parts of metallic carbon nanotubes, 25 parts of nano-tin oxide and deionized water are added to a reaction vessel and mixed evenly by low-speed stirring. Then, acetic acid acid regulator is slowly added to adjust the pH value to acidic. Then, while stirring, a mixed solution of 7.3 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560) and anhydrous ethanol is slowly added. After the addition is completed, the temperature is raised to 65°C and the reaction is maintained at this temperature for 2.5 h. After the reaction is completed, the mixture is cooled to room temperature and centrifuged. Then, the lower precipitate is taken and dispersed in anhydrous ethanol, and then sonicated for 1 h. Finally, it is dried at 80°C for 12 h to obtain the modified powder.

[0057] The preparation method of the radiation-resistant and photothermal dual-curing conductive adhesive in this embodiment includes the following steps:

[0058] S1. Start the stirring in the reactor at a speed of 300 r / min. While stirring, add 19.6 parts of hydrogenated bisphenol A epoxy resin, 5.8 parts of phenolic epoxy acrylate, and 4 parts of oxetane epoxy reactive diluent. After the addition is complete, mix and stir for 5 minutes, reserving 2 parts of oxetane epoxy reactive diluent.

[0059] S2. Increase the rotation speed to 900 r / min and gradually add 73 parts of modified powder while stirring;

[0060] S3. Increase the rotation speed to 1400 r / min and stir rapidly for 50 min until the modified powder is completely and evenly dispersed.

[0061] S4. Adjust the speed to 900r / min, add 6 parts of organic flame retardant while stirring, and stir for 5min.

[0062] S5. While stirring, add 1.2 parts of cationic thermal initiator CTI-100, 1.2 parts of free radical photoinitiator 819, 1.5 parts of p-(octoxyphenyl)phenyliodonium hexafluoroantimonate, and 2.5 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560) and stir for 5 min.

[0063] S6. Stop stirring and test the viscosity of the mixed slurry. Based on the viscosity test results of the mixed slurry, add an appropriate amount of 2 parts of oxetane epoxy reactive diluent to the mixed slurry and adjust the mixed slurry to the target viscosity to obtain conductive adhesive.

[0064] Example 2: This example also provides a radiation-resistant photothermal dual-curing conductive adhesive, comprising the following components by weight: 19.6 parts hydrogenated bisphenol A epoxy resin, 5.8 parts phenolic epoxy acrylate, 73 parts modified powder, 1.2 parts cationic thermal initiator CTI-100, 1.2 parts free radical photoinitiator 819, 1.5 parts p-(octyloxyphenyl)phenyliodonium hexafluoroantimonate, 6 parts oxetane epoxy reactive diluent, 2.5 parts γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), and 6 parts organic flame retardant.

[0065] The preparation method of the modified powder is as follows: 30 parts of conductive mica powder, 18 parts of metallic carbon nanotubes, 25 parts of nano tin oxide and deionized water are added to a reaction vessel and mixed evenly by low-speed stirring. Then, acetic acid acid regulator is slowly added to adjust the pH value to acidic. Then, while stirring, a mixed solution of 7.3 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560) and anhydrous ethanol is slowly added. After the addition is completed, the temperature is raised to 65°C and the reaction is maintained at this temperature for 2.5 h. After the reaction is completed, the mixture is cooled to room temperature and centrifuged. Then, the lower precipitate is taken and dispersed in anhydrous ethanol, and then sonicated for 1 h. Finally, it is dried at 80°C for 12 h to obtain the modified powder.

[0066] The preparation method of the radiation-resistant photothermal dual-curing conductive adhesive in this embodiment is the same as that in Embodiment 1.

[0067] Example 3: This example also provides a radiation-resistant photothermal dual-curing conductive adhesive, comprising the following components by weight: 6.7 parts alicyclic epoxy resin, 3.3 parts o-cresol epoxy acrylate, 30 parts modified powder, 1 part cationic thermal initiator CTI-150, 1 part free radical photoinitiator 369, 1 part phenylthiophenyl-diphenylthionium hexafluorophosphate, 5 parts β-hydroxyethyl methacrylate epoxy reactive diluent, and 1 part γ-methacryloyloxypropyltrimethoxysilane (KH570).

[0068] The preparation method of the modified powder is as follows: 19 parts of conductive titanium dioxide, 4 parts of metallic carbon nanotubes, 5 parts of nano tantalum oxide and deionized water are added to a reaction vessel and mixed evenly by low-speed stirring. Then, acetic acid acid regulator is slowly added to adjust the pH value to acidic. Then, while stirring, a mixed solution of 3.4 parts of γ-methacryloyloxypropyltrimethoxysilane (KH570) and anhydrous ethanol is slowly added. After the addition is completed, the temperature is raised to 65°C and the reaction is maintained at this temperature for 2.5 h. After the reaction is completed, the mixture is cooled to room temperature and centrifuged. Then, the lower precipitate is taken and dispersed in anhydrous ethanol, and then sonicated for 1 h. Finally, it is dried at 70°C for 12 h to obtain the modified powder.

[0069] This embodiment also provides a method for preparing the above-mentioned radiation-resistant photothermal dual-curing conductive adhesive, comprising the following steps:

[0070] S1. Start the stirring in the reactor at a speed of 100r / min. While stirring, add 6.7 parts of alicyclic epoxy resin, 3.3 parts of o-cresol epoxy acrylate, and 3 parts of methacrylate-β-hydroxyethyl ester epoxy reactive diluent. After the addition is complete, mix and stir for 5 minutes, reserving 2 parts of methacrylate-β-hydroxyethyl ester epoxy reactive diluent.

[0071] S2. Increase the rotation speed to 800 r / min and gradually add 30 parts of modified powder while stirring;

[0072] S3. Increase the rotation speed to 1200 r / min and stir rapidly for 50 min until the modified powder is completely and evenly dispersed;

[0073] S4. While stirring, add 1 part of cationic thermal initiator CTI-150, 1 part of free radical photoinitiator 369, 1 part of phenylthiophenyl-diphenylthionium hexafluorophosphate, and 1 part of γ-methacryloyloxypropyltrimethoxysilane (KH570), and stir for 5 min.

[0074] S5. Stop stirring and test the viscosity of the mixed slurry. Based on the viscosity test results of the mixed slurry, add an appropriate amount of 2 parts of methacrylate-β-hydroxyethyl ester epoxy reactive diluent to the mixed slurry and adjust the mixed slurry to the target viscosity to obtain conductive adhesive.

[0075] Example 4: This example also provides a radiation-resistant photothermal dual-curing conductive adhesive, comprising the following components by weight: 25 parts hydrogenated bisphenol A epoxy resin, 5 parts phenolic epoxy acrylate, 60 parts modified powder, 5 parts cationic thermal initiator CTI-100, 2 parts free radical photoinitiator 819, 2 parts p-(octoxyphenyl)phenyl iodonium hexafluoroantimonate, 10 parts oxetane epoxy reactive diluent, and 1 part organic flame retardant.

[0076] The preparation method of the modified powder is as follows: 22 parts of silver-plated graphite, 20 parts of metallic carbon nanotubes, 16.2 parts of nano-zirconia and deionized water are added to a reaction vessel and mixed evenly by low-speed stirring. Then, acetic acid acid regulator is slowly added to adjust the pH value to acidic. Subsequently, while stirring, a mixed solution of 5.4 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560) and anhydrous ethanol is slowly added. After the addition is completed, the temperature is raised to 65°C and the reaction is maintained at this temperature for 2.5 h. After the reaction is completed, the mixture is cooled to room temperature and centrifuged. The lower precipitate is then dispersed in anhydrous ethanol and sonicated for 1 h. Finally, it is dried at 80°C for 12 h to obtain the modified powder.

[0077] This embodiment also provides a method for preparing the above-mentioned radiation-resistant photothermal dual-curing conductive adhesive, comprising the following steps:

[0078] S1. Start the stirring in the reactor at a speed of 400r / min. While stirring, add 25 parts of hydrogenated bisphenol A epoxy resin, 5 parts of phenolic epoxy acrylate, and 5 parts of oxetane epoxy reactive diluent. After the addition is complete, mix and stir for 5 minutes, reserving 5 parts of oxetane epoxy reactive diluent.

[0079] S2. Increase the rotation speed to 1000 r / min and gradually add 60 parts of modified powder while stirring;

[0080] S3. Increase the rotation speed to 1500 r / min and stir rapidly for 50 min until the modified powder is completely and evenly dispersed.

[0081] S4. Adjust the speed to 1000r / min, add 1 part of organic flame retardant while stirring, and stir for 5min.

[0082] S5. Keep the rotation speed at 1000r / min, and while stirring, add 5 parts of cationic thermal initiator CTI-100, 2 parts of free radical photoinitiator 819, and 2 parts of p-(octyloxyphenyl)phenyliodonium hexafluoroantimonate, and stir for 5min;

[0083] S6. Stop stirring and test the viscosity of the mixed slurry. Based on the viscosity test results of the mixed slurry, add an appropriate amount of 5 parts of oxetane epoxy reactive diluent to the mixed slurry and adjust the mixed slurry to the target viscosity to obtain conductive adhesive.

[0084] Example 5: This example also provides a radiation-resistant photothermal dual-curing conductive adhesive, comprising the following components by weight: 10 parts hydrogenated bisphenol A epoxy resin, 10 parts o-cresol epoxy acrylate, 75 parts modified powder, 3 parts cationic thermal initiator CTI-200, 1.5 parts free radical photoinitiator 907, 1.5 parts triarylhexafluorophosphate thioonium salt, 8 parts oxetane epoxy reactive diluent, 2 parts γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), and 3 parts organic flame retardant.

[0085] The preparation method of the modified powder is as follows: 32 parts of conductive mica powder, 29.6 parts of metallic carbon nanotubes, 11.6 parts of nano tin oxide and deionized water are added to a reaction vessel and mixed evenly by low-speed stirring. Then, acetic acid acid regulator is slowly added to adjust the pH value to acidic. Subsequently, a mixed solution of 5.8 parts of vinyltrimethoxysilane (KH-171) and anhydrous ethanol is slowly added while stirring. After the addition is completed, the temperature is raised to 65°C and the reaction is maintained at this temperature for 2.5 hours. After the reaction is completed, the mixture is cooled to room temperature and centrifuged. The lower precipitate is then dispersed in anhydrous ethanol and sonicated for 1 hour. Finally, it is dried at 80°C for 12 hours to obtain the modified powder.

[0086] The preparation method of the radiation-resistant and photothermal dual-curing conductive adhesive in this embodiment includes the following steps:

[0087] S1. Start the stirring in the reactor at a speed of 300r / min. While stirring, add 10 parts of hydrogenated bisphenol A epoxy resin, 10 parts of o-cresol epoxy acrylate, and 5 parts of oxetane epoxy reactive diluent. After the addition is complete, mix and stir for 5 minutes, reserving 3 parts of oxetane epoxy reactive diluent.

[0088] S2. Increase the rotation speed to 900 r / min and gradually add 75 parts of modified powder while stirring;

[0089] S3. Increase the rotation speed to 1400 r / min and stir rapidly for 50 min until the modified powder is completely and evenly dispersed.

[0090] S4. Adjust the speed to 900 r / min, add 3 parts of organic flame retardant while stirring, and stir for 5 min.

[0091] S5. While stirring, add 3 parts of cationic thermal initiator CTI-200, 1.5 parts of free radical photoinitiator 907, 1.5 parts of triarylhexafluorophosphate thioonium salt, and 2 parts of vinyltrimethoxysilane (KH-171), and stir for 5 minutes.

[0092] S6. Stop stirring and test the viscosity of the mixed slurry. Based on the viscosity test results of the mixed slurry, add an appropriate amount of 3 parts of oxetane epoxy reactive diluent to the mixed slurry and adjust the mixed slurry to the target viscosity to obtain conductive adhesive.

[0093] Example 6: This example also provides a radiation-resistant photothermal dual-curing conductive adhesive, comprising the following components by weight: 10 parts hydrogenated bisphenol A epoxy resin, 5 parts phenolic epoxy acrylate, 45 parts modified powder, 2.5 parts cationic thermal initiator CTI-100, 1.5 parts free radical photoinitiator 819, 1 part p-(octoxyphenyl)phenyliodonium hexafluoroantimonate, 7 parts oxetane epoxy reactive diluent, 1.5 parts γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), and 10 parts organic flame retardant.

[0094] The preparation method of the modified powder is as follows: 15.5 parts of silver-plated copper powder, 12.5 parts of metallic carbon nanotubes, 14.5 parts of nano-tin oxide and deionized water are added to a reaction vessel and mixed evenly by low-speed stirring. Then, acetic acid acid regulator is slowly added to adjust the pH value to acidic. Subsequently, while stirring, a mixed solution of 3.1 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560) and anhydrous ethanol is slowly added. After the addition is completed, the temperature is raised to 65°C and the reaction is maintained at this temperature for 2.5 h. After the reaction is completed, the mixture is cooled to room temperature and centrifuged. The lower precipitate is then dispersed in anhydrous ethanol and sonicated for 1 h. Finally, it is dried at 80°C for 12 h to obtain the modified powder.

[0095] The preparation method of the radiation-resistant and photothermal dual-curing conductive adhesive in this embodiment includes the following steps:

[0096] S1. Start the stirring in the reactor at a speed of 300r / min. While stirring, add 10 parts of hydrogenated bisphenol A epoxy resin, 5 parts of phenolic epoxy acrylate, and 5 parts of oxetane epoxy reactive diluent. After the addition is complete, mix and stir for 5 minutes, reserving 2 parts of oxetane epoxy reactive diluent.

[0097] S2. Increase the rotation speed to 900 r / min and gradually add 45 parts of modified powder while stirring;

[0098] S3. Increase the rotation speed to 1400 r / min and stir rapidly for 50 min until the modified powder is completely and evenly dispersed;

[0099] S4. Adjust the speed to 900r / min, add 10 parts of organic flame retardant while stirring, and stir for 5min.

[0100] S5. While stirring, add 2.5 parts of cationic thermal initiator CTI-100, 1.5 parts of free radical photoinitiator 819, 1 part of p-(octoxyphenyl)phenyliodonium hexafluoroantimonate, and 1.5 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560) and stir for 5 min.

[0101] S6. Stop stirring and test the viscosity of the mixed slurry. Based on the viscosity test results of the mixed slurry, add an appropriate amount of 2 parts of oxetane epoxy reactive diluent to the mixed slurry and adjust the mixed slurry to the target viscosity to obtain conductive adhesive.

[0102] Comparative Example 1

[0103] A radiation-resistant, photothermal dual-curing conductive adhesive comprises the following components by weight: 10 parts hydrogenated bisphenol A epoxy resin, 5 parts phenolic epoxy acrylate, 45 parts powder, 2.5 parts cationic thermal initiator CTI-100, 1.5 parts free radical photoinitiator 819, 1 part p-(octoxyphenyl)phenyliodonium hexafluoroantimonate, 7 parts oxetane epoxy reactive diluent, 1.5 parts γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), and 10 parts organic flame retardant. The preparation method of the radiation-resistant, photothermal dual-curing conductive adhesive is the same as in Example Six.

[0104] The powder comprises the following components by weight: 15.5 parts silver-plated copper powder, 12.5 parts metallic carbon nanotubes, and 14.5 parts nano tin oxide.

[0105] Comparative Example 2

[0106] A radiation-resistant conductive adhesive comprises the following components by weight: 15 parts phenolic epoxy acrylate, 45 parts modified powder, 2.5 parts cationic thermal initiator CTI-100, 7 parts oxobutane epoxy reactive diluent, 1.5 parts γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), and 10 parts organic flame retardant. The preparation method of the radiation-resistant conductive adhesive is the same as in Example Six.

[0107] The preparation method of the modified powder is as follows: 15.5 parts of silver-plated copper powder, 12.5 parts of metallic carbon nanotubes, 14.5 parts of nano-tin oxide and deionized water are added to a reaction vessel and mixed evenly by low-speed stirring. Then, acetic acid acid regulator is slowly added to adjust the pH value to acidic. Subsequently, while stirring, a mixed solution of 3.1 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560) and anhydrous ethanol is slowly added. After the addition is completed, the temperature is raised to 65°C and the reaction is maintained at this temperature for 2.5 h. After the reaction is completed, the mixture is cooled to room temperature and centrifuged. The lower precipitate is then dispersed in anhydrous ethanol and sonicated for 1 h. Finally, it is dried at 80°C for 12 h to obtain the modified powder.

[0108] Comparative Example 3

[0109] A radiation-resistant, photothermal dual-curing conductive adhesive comprises the following components by weight: 10 parts hydrogenated bisphenol A epoxy resin, 5 parts phenolic epoxy acrylate, 45 parts modified powder, 2.5 parts cationic thermal initiator CTI-100, 1.5 parts free radical photoinitiator 819, 1 part p-(octoxyphenyl)phenyliodonium hexafluoroantimonate, 7 parts oxetane epoxy reactive diluent, 1.5 parts γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), and 10 parts organic flame retardant. The preparation method of the radiation-resistant, photothermal dual-curing conductive adhesive is the same as in Example Six.

[0110] The preparation method of the modified powder is as follows: 15.5 parts of silver-plated copper powder, 27 parts of metallic carbon nanotubes and deionized water are added to a reaction vessel and mixed evenly by low-speed stirring. Then, acetic acid acid regulator is slowly added to adjust the pH value to acidic. Subsequently, a mixed solution of 3.1 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560) and anhydrous ethanol is slowly added while stirring. After the addition is completed, the temperature is raised to 65°C and the reaction is maintained at this temperature for 2.5 h. After the reaction is completed, the mixture is cooled to room temperature and centrifuged. The lower precipitate is then dispersed in anhydrous ethanol and sonicated for 1 h. Finally, it is dried at 80°C for 12 h to obtain the modified powder.

[0111] The radiation resistance, volume resistivity, and bleeding width of the conductive adhesives used in Examples 1 to 6 and Comparative Examples 1 to 3 were tested below. The radiation resistance was tested at the device level. Specifically, the conductive adhesives were applied to devices with the same thickness and application method, and the devices were subjected to environmental aging using a total radiation dose of 80 krad. The failure rate of the devices after aging was then measured. The volume resistivity was measured using the four-point probe method. The bleeding width was measured using a metallographic microscope, and the bleeding width of the conductive adhesive was recorded under the same waiting time.

[0112] Table 1. Radiation resistance, volume resistivity, and bleeding width of the conductive adhesives in each embodiment and comparative example.

[0113]

[0114] As can be seen from Table 1, the conductive adhesives of Examples 1 to 6 of the present invention can significantly improve the radiation resistance, reduce the device failure rate and bleeding width.

[0115] Compared to Comparative Example 1, Example 6 effectively improved radiation resistance and suppressed bleeding by modifying the powder; compared to Comparative Example 2, Example 6 significantly suppressed bleeding by adding photocurable resin and photoinitiator, which can be used for photothermal dual curing; compared to Comparative Example 3, Example 6 greatly improved radiation resistance by controlling the content of each component in the modified powder.

[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A radiation-resistant and photothermal dual-curing conductive adhesive, characterized in that, The product comprises the following components by weight: 10-30 parts epoxy resin, 1-5 parts thermal initiator, 2-4 parts photoinitiator, 30-75 parts modified powder, 0-3 parts coupling agent, 5-10 parts epoxy reactive diluent, and 0-10 parts flame retardant; the modified powder is prepared by modifying a mixture of conductive filler, metallic carbon nanotubes, and nano-metal oxides with a modifier.

2. The radiation-resistant and photothermal dual-curing conductive adhesive as described in claim 1, characterized in that: The amount of the conductive filler is 20-50% of the total mass of the conductive adhesive; the amount of the metallic carbon nanotubes is 8-26% of the total mass of the conductive adhesive; and the amount of the nano-metal oxide is 10-25% of the total mass of the conductive adhesive.

3. The radiation-resistant and photothermal dual-curing conductive adhesive as described in claim 1, characterized in that: The conductive filler includes at least one of conductive mica powder, conductive titanium dioxide, conductive barium sulfate, conductive silicon dioxide, silver-plated copper powder, silver-plated nickel powder, and silver-plated graphite; the nano-metal oxide includes at least one of nano-tin oxide, nano-tantalum oxide, and nano-zirconia; and the modifier is a silane coupling agent.

4. The radiation-resistant and photothermal dual-curing conductive adhesive as described in claim 1, characterized in that: The modified powder is prepared by stirring and mixing conductive filler, metallic carbon nanotubes, nano-metal oxides and deionized water evenly, adjusting the pH value to acidic, then adding a mixed solution of modifier and anhydrous ethanol to carry out the modification reaction. After the reaction is completed, the mixture is cooled to room temperature, centrifuged and the lower precipitate is dispersed in anhydrous ethanol, then sonicated and dried to obtain the modified powder.

5. The radiation-resistant and photothermal dual-curing conductive adhesive as described in claim 4, characterized in that: The ratio of the total mass of the conductive filler, the metallic carbon nanotubes, and the nano-metal oxides to the mass of the modifier is 100:(5-12).

6. The radiation-resistant and photothermal dual-curing conductive adhesive as described in claim 1, characterized in that: The epoxy resin includes thermosetting epoxy resin and photocuring epoxy resin, and the mass ratio of the thermosetting epoxy resin to the photocuring epoxy resin is (1-5):

1.

7. The radiation-resistant and photothermal dual-curing conductive adhesive as described in claim 1, characterized in that: The thermal initiator is a cationic thermal initiator; the photoinitiator includes a free radical photoinitiator and a cationic photoinitiator, and the mass ratio of the two is (1-2):(1-2).

8. A method for preparing the radiation-resistant photothermal dual-curing conductive adhesive according to any one of claims 1-7, characterized in that, Includes the following steps: S1. The reactor is stirred at the first speed, and epoxy resin and part of epoxy reactive diluent are added while stirring. S2. Increase the rotation speed to the second speed and gradually add the modified powder while stirring; S3. Increase the rotation speed to the third speed and stir until the modified powder is completely and evenly dispersed; S4. Adjust the speed to the second speed, add the flame retardant while stirring, and stir until the mixture is evenly mixed. S5. Keep the rotation speed at the second speed and add the thermal initiator, photoinitiator and coupling agent while stirring; S6. Stop stirring, test the viscosity of the mixed slurry, and use the remaining epoxy reactive diluent to adjust the mixed slurry to the target viscosity.

9. The preparation method according to claim 8, characterized in that: In step S3, after stirring until the modified powder is completely and evenly dispersed, test the fineness of the mixed slurry. If it does not meet the standard, continue stirring until the target fineness is reached. During the stirring process, keep the temperature of the mixed slurry at 10-35℃.

10. The preparation method according to claim 8, characterized in that: The first rotational speed is 100-400 r / min, the second rotational speed is 800-1000 r / min, and the third rotational speed is 1200-1500 r / min.